Solid phase extraction of phenolics using sorbents based on porous organic polymers - Heinrich, Kayla (Stellenbosch : Stellenbosch University, 2023)
Heinrich, Kayla. 2023. Solid phase extraction of phenolics using sorbents based on porous organic polymers. Unpublished master's dissertation. Stellenbosch : Stellenbosch University [online]. Available at: https://scholar.sun.ac.za/items/80080136-6c04-4b9a-8c9d-29894761b6ed/